2004
DOI: 10.1074/jbc.m313119200
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Chemosensory Cilia Cause Resistance to Paraquat in Nematode Caenorhabditis elegans

Abstract: The relationship between oxidative stress and longevity is a matter of concern in various organisms. We isolated mutants resistant to paraquat from nematode Caenorhabditis elegans. One mutant named mev-4 was longlived and showed cross-resistance to heat and Dyf phenotype (defective in dye filling). Genetic and sequence analysis revealed that mev-4 had a nonsense mutation on the che-11 gene, homologues of which are involved in formation of cilia and flagella in other organisms. The paraquat resistance was commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 65 publications
3
26
0
Order By: Relevance
“…This channel is absent in dye‐filling mutants ( dyf ), such as osm‐3(p802) that lack amphid neurons and, as a result, are resistant to the inhibitory effect of paraquat on development (Fujii et al ., 2004). We confirmed the resistance of osm‐3(p802) larvae to the paraquat‐induced block in development (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This channel is absent in dye‐filling mutants ( dyf ), such as osm‐3(p802) that lack amphid neurons and, as a result, are resistant to the inhibitory effect of paraquat on development (Fujii et al ., 2004). We confirmed the resistance of osm‐3(p802) larvae to the paraquat‐induced block in development (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that resistance to paraquat partially results from the inability to take up paraquat into chemosensory neurons (30). In our experiments, hNgb/EGFP was expressed pan-neuronally.…”
Section: The Tg Worms and Glb-13 Mutants Have No Deviant Fluorescein mentioning
confidence: 55%
“…In our experiments, hNgb/EGFP was expressed pan-neuronally. Therefore, we tested whether the paraquat resistance of hNgb-Tg worms resulted from a defect in chemosensory neurons (30). Our results showed that chemosensory neurons of N2 and Tg worms were clearly stained (Fig.…”
Section: The Tg Worms and Glb-13 Mutants Have No Deviant Fluorescein mentioning
confidence: 95%
See 2 more Smart Citations